Elemental image and audio synchronization and transmission technique for glasses-free 3D TV system - Khan, Amit Hasan; Khan, Fairoz Nower; Nisa, Noor E; Jannat, Ashraful (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.